Implementasi Model Pembelajaran GI (Group Investigation) untuk Meningkatkan Hasil Belajar IPA Tema 9 “Menjelajah Angkasa Luar” bagi Siswa Kelas VI SD Negeri Tlogosari Kulon 03 Semarang - Rubiyati Rubiyati (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Based on the background of the problems described above, several problems can be identified as follows: students who are less able to master science learning in class VI even semester at SD Negeri Tlogosari Kulon 03. Out of 39 children, only 14 children (35.90%) achieved the KKM. The teacher's efforts to improve the ability of science learning outcomes Theme 9